Vision improvement in severe acute isolated optic neuritis after plasma exchange treatment in Chinese population: a prospective case series study. (August 2020) - Tan, Shaoying; Ng, Tsz Kin; Xu, Quangang; Yang, Mo; Zhuang, Yuan; Zhao, Jie; Zhou, Huanfen; Teng, Da; Wei, Shihui
Background: Plasma exchange (PE) is often considered as an effective treatment for neuromyelitis optica spectrum disorder (NMOSD) and several inflammatory demyelinating disorders of the central nervous system. This study aimed to evaluate the visual outcomes of Chinese patients with severe acute isolated optic neuritis (ON) who received PE therapy after high-dose intravenous methylprednisolone (IVMP) treatment. Methods: Thirty-seven acute isolated ON patients experiencing their first attack of severe visual impairment without neurological disability were recruited. All subjects received five cycles of double-filtration plasmapheresis. Visual acuity (VA) was documented at onset, 1 day before PE treatment, at each cycle of PE therapy and at the 1-month follow-up visit. Results: This study included 26 female (70.3%) and 11 male (29.7%) subjects, and 18 subjects (48.6%) had bilateral involvement. The time window between onset and PE treatment was 27.3 ± 12.7 days (range: 6–53 days). Mean VA (logMAR) of the studied eyes at onset, 1-day before PE treatment/after IVMP and after the fifth PE treatment were 3.41 ± 1.50, 2.61 ± 1.64 and 1.66 ± 1.52, respectively ( p  < 0.001). Nineteen eyes (51.4%) showed no light perception at the onset, and 17 eyes (45.9%) improved to Snellen VA >20/800 after IVMP and PE treatments, among which five eyes (13.5%) recovered to Snellen VA 20/20 ( p  < 0.001). Predictors of good visual outcome included body mass index [odds ratio (OR) = 0.734, p  = 0.044], serum AQP4 antibody-positive status (OR = 0.004, p  = 0.001), bilaterality (OR = 0.042, p  = 0.008) and time window from onset to PE therapy per 1 day (OR = 0.79, p  = 0.002). Conclusion: This study revealed that PE treatment effectively improves the visual outcomes of patients experiencing their first attack of severe acute isolated ON after high-dose IVMP treatment. Better visual outcomes can be achieved with early PE treatment.